(untitled) (Revista Electrónica REDINE, 2018)
The present study had as objective to describe the Scientific Productivity of the Teachers of the Department of Nursing of the Dean of Health Sciences. The research is of a quantitative and documentary nature. A review of the scientific productivity of 83 teachers was carried out, in the registers of the Council for Scientific, Humanistic and Technological Development (CDCHT), in Ascension or Postgraduate work of the Library, in the Research Unit and in the web, Work through the phases of: review, detection, consultation, extraction, collection and integration of relevant information with the objectives of the research. The data were analyzed and interpreted using descriptive statistics. The most outstanding results were: Teachers fulfilled the research function through tutorials, publications in scientific journals and promotion works, with the highest percentage of publications in 2008, 2011 and 2014 being highlighted. Likewise, the predominant publications Represented original articles, articles of reflection and essays. In addition, a small percentage was found corresponding to projects registered in the CDCHT, some of which culminated in promotion work and publications. With regard to project financing, the highest percentage was for non-funded projects. The research areas developed in higher percentage: Educational Research in Nursing and Nursing in Community Health and to a lesser extent: Management in Nursing, Nursing in Reproductive Health and Nursing in Adult Care.